The Protection of Medical Officers in the Armed Conficts; Case Study of Indonesia - Mahfud Abdullah (Faculty of Law, Jambi University, 2020)
International Humanitarian Law (HHI) has regulated provisions regarding the protection of medical personnel in a conflict, whether an international, non-international armed conflict or an internationalized armed conflict. These categories of various types of armed conflict are also part of the legality of the emergence of humanitarian intervention by medical personnel in an armed conflict. A form of medical care for parties who are either directly or indirectly involved in an armed conflict. In the Indonesian context, the provisions regulating separately the protection of medical personnel in armed conflict have not been regulated separately. However, considering that Indonesia has ratified the 1949 Geneva Convention, the convention can be considered as the official Indonesian national regulation on the protection of medical personnel in armed conflict. In this article, it is demonstrated that there were still many violations, especially against the purpose of war, which made medical officers and medical buildings in an armed conflict a military target, such as in the Syrian conflict, as well as domestic Indonesia such as Aceh and Papua. Several factors have led to the fall of medical personnel in various armed conflicts (both horizontal and vertical) in Indonesia, among others are: (a) The parties to an armed conflict are not aware of the provisions of the principles of international humanitarian law. (b) The parties are suspicious of the neutrality of the medical personnel, as well as (c) Not having a good communication system between the conflicting parties and medical personnel.